2012
DOI: 10.1093/scan/nss077
|View full text |Cite
|
Sign up to set email alerts
|

A selective role for right insula—basal ganglia circuits in appetitive stimulus processing

Abstract: Hemispheric lateralization of hedonic evaluation ('liking') and incentive motivation ('wanting') in neural networks connecting the basal ganglia and insula (BG-I) in humans was examined. Participants with brain damage restricted to the BG-I of the right (n = 5) or left (n = 5) hemisphere, and 26 healthy participants matched on age, sex and intelligence quotient were tested on positively and negatively valenced pictures drawn from varied stimulus categories (Vijayaraghavan et al., 2008). Liking was assessed wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 39 publications
1
7
0
Order By: Relevance
“…Our study provides the first empirical evidence that basic emotions like SEEKING, SADNESS, FEAR, and ANGER are affected by stroke in general and specific lesion locations in particular. These results can find some correspondences with other studies relative to the motivational system of emotions in brain-damaged patients (e.g., Feinstein et al, 2013;Vijayaraghavan et al, 2013) This is well in line with both neuroscientific and clinical evidence. Neuroscientifically, basic emotions have been associated with mainly subcortical and medial regions in the brain; this is congruent with the various emotional changes following specific lesion locations observed in our study.…”
Section: Stroke and Basic Emotionssupporting
confidence: 90%
“…Our study provides the first empirical evidence that basic emotions like SEEKING, SADNESS, FEAR, and ANGER are affected by stroke in general and specific lesion locations in particular. These results can find some correspondences with other studies relative to the motivational system of emotions in brain-damaged patients (e.g., Feinstein et al, 2013;Vijayaraghavan et al, 2013) This is well in line with both neuroscientific and clinical evidence. Neuroscientifically, basic emotions have been associated with mainly subcortical and medial regions in the brain; this is congruent with the various emotional changes following specific lesion locations observed in our study.…”
Section: Stroke and Basic Emotionssupporting
confidence: 90%
“…Furthermore, a meta-representation of primary interoceptive activity is engendered in the right anterior insula, which seems to provide the basis for the subjective image of the material self as a feeling entity (i.e., emotional awareness) 36 . A previous study has reported that the right insular cortex plays a greater role than the left in supporting reward evaluation and motivational approaches to positive stimuli 37 . An additional study has noted that the perceived warmth of a mother’s infant was correlated with activation in her right AIC when viewing her infant 33 .…”
Section: Discussionmentioning
confidence: 99%
“…given similar expected reward, a high density of low reward possibilities was associated with greater insular activation. In addition, enhancement of the hedonic (Vijayaraghavan et al, 2012) and incentive (Chaudhry et al, 2009) values of an option by both cognitive and affective processes involves the insular cortex. Some investigators have found an exaggerated insula response to monetary reward reception in abstinent cocaine dependent individuals (Jia et al, 2011) and marijuana users (Cousijn et al, 2012) whereas others have found hypoactivity in the left insula cortex in response to loss and loss avoidance outcome notifications in cannabis users (Nestor et al, 2010).…”
Section: The Interface Between Interoception and Basic Behavioral mentioning
confidence: 99%